Chapter 12. Onion, Leek, and Chive Production in Florida - Hugh Smith; Johan Desaeger; Peter J. Dittmar; Pamela Roberts; Xavier Martini; Shouan Zhang; Lincoln Zotarelli (EDIS)
Chapter 12 of the Vegetable Production Handbook.